Multi-wavelength measurements of aerosol optical absorption coefficients using a photoacoustic spectrometer - 刘强 黄宏华 王尧 王贵师 曹振松 刘锟 陈卫东 高晓明 (Chinese physics B, 2014)
The atmospheric aerosol absorption capacity is a critical parameter determining its direct and indirect effects on cli- mate. Accurate measurement is highly desired for the study of the radiative budget of the Earth. A multi-wavelength （405 rim, 532 nm, 780 nm） aerosol absorption meter based on photoacoustic spectroscopy （PAS） invovling a single cylin- drical acoustic resonator is developed for measuring the aerosol optical absorption coefficients （OACs）. A sensitivity of 1.3 Mm-l （at 532 nm） is demonstrated. The aerosol absorption meter is successfully tested through measuring the OACs of atmospheric nigrosin and ambient aerosols in the suburbs of Hefei city. The absorption cross section and absorption Angstrom exponent （AAE） for ambient aerosol are determined for characterizing the component of the ambient aerosol.